MODUL NEUTROSOFIK KUAT - Suryoto Suryoto; Harjito Harjito; Titi Udjiani (Diponegoro University, 2018)
Given any neutrosophic ring with unity and a commutatively additive neutrosophic group. Then we can formed a neutrosophic algebraic structure is called a strong neutrosphic module. From the concept of weak neutrosophic module we extend to the concept of strong neutrosophic module. In this paper, also elementary properties of strong neutrosophic module are given.